DC reactive sputter deposition of CuO thin films at different operating pressures. (2018) - Sangwaranatee, N.W.; Sangwaranatee, N.; Horprathum, M.; Chananonnawathorn, C.; Muntini, M.
Abstract: Copper oxide (CuO) thin films were prepared on glass slide and silicon wafer substrates using dc reactive magnetron sputtering at different operating pressure. The high purity Cu target was used, and sputtering was carried out in argon and oxygen atmosphere. The operating pressure was varied from 10 to 40 mTorr. The physical microstructure and optical properties were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and spectrophotometer. For the crystal structure, the XRD results indicated that the prepared CuO thin films were polycrystalline with monoclinic structure. The FE-SEM results demonstrated the increased of the dense pack structure for the films deposited at low operating pressure. The average optical transmittance at visible region of the film was about ∼50%.